Defining, locating, and addressing bullying in the WPA workplace - Elder, Cristyn L.; Davila, Bethany (Utah State University Press, 2018)
"The first volume to take up bullying in writing programs. Contributors share their personal stories and analyze varieties of collegial malevolence they have experienced as WPAs, with consequences in emotional, mental, and physical health, and in personal and institutional economies"--Provided by publisher